Polish Non-treasury Bond Market – New Bond Registration Rules and Analysis of the Bond Issuers’ Register - Martysz, Czesław Bartłomiej (Journal of Finance and Financial Law, 2020)
After the Getback S.A. scam, a special Bond Issuers’ Register (RZE) was created to strengthen market supervision, which makes it easier for investors to search for information on debt securities. Thanks to this register, we can finally learn about the actual size and several important features of the Polish non-Treasury debt securities market. The first objective of the article is to show significant changes in the law concerning the form of registration of bonds and their potential impact on further market development. The second goal is to show the previously unknown scale and main features of the bond market, including in particular municipal bonds. The first hypothesis is that the obligatory registration of bonds in KDPW together with the publicly available Bond Issuers’ Register (RZE) have improved the transparency and security level of the Polish non-treasury bond market and facilitated trading in these securities on the secondary market. The second hypothesis is that the Bond Issuers’ Register is the first publicly available tool for a comprehensive analysis of the Polish non-treasury bond market, which revealed, among other things, the high fragmentation of issuers (especially in local government bonds), the dominance of state-controlled issuers, the predominance of floating rate bonds and a significant size of the bond market registered outside KDPW.